FACTORS INFLUENCING AUDIT DELAY IN PUBLICLY LISTED COMPANIES - Cristino Gusmao; Aprih Santoso; Kampono Imam Yulianto; Nirsetyo Wahdi (CV. Fahr Publishing, 2025)
This study aims to examine the factors that influence audit delay in publicly listed companies, with a specific focus on integrating corporate characteristics, auditor profiles, governance structures, and contextual variables in an emerging market setting. Employing a quantitative explanatory method, data were collected through structured questionnaires from 80 respondents comprising accounting teachers and internship supervisors in five public vocational schools (SMK) in Jakarta, which collaborate with listed companies. The data were analyzed using multiple linear regression with IBM SPSS 26 to test the effect of firm size, auditor type, governance structure, financial loss, and operational complexity on audit delay. The findings reveal that firm size, auditor type, and governance structure significantly affect audit delay, while financial loss and complexity do not show a statistically significant influence. The novelty of this study lies in its integration of vocational education perspectives into audit research and its inclusion of digital readiness and post-pandemic factors as contextual variables—elements that are still rarely addressed in previous literature. Furthermore, the study introduces an interdisciplinary lens by connecting audit performance with real-world educational experiences, offering theoretical enrichment and practical implications for improving audit timeliness. In conclusion, this research highlights the evolving determinants of audit delay beyond traditional financial indicators and supports the development of more responsive audit frameworks, especially in countries undergoing regulatory and technological transitions.